Warehouse material handling layout planning using the activity relationship chart method and blocplan 90 - Syahreen Nurmutia (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
This research aims to plan the layout of material handling in a warehouse using the Activity Relationship Chart (ARC) method which is supported by the application of Blocplan 90. In warehouse management, the layout of material handling plays a crucial role in operational efficiency and productivity. The ARC method is used to identify relationships between activities in the material handling process and Blocplan 90 is used as a tool to optimally arrange the warehouse layout. This research will involve analysis of various material handling activities, including storing, picking, and moving goods. By paying attention to the interrelationships between activities revealed by ARC, this research will produce layout recommendations that can increase efficiency, reduce travel time, and minimize the risk of accidents and damage to goods. It is hoped that the results of this research can provide practical guidance for warehouse planners to improve operational performance and optimize the use of storage space. Thus, this research provides a significant contribution in the context of logistics management and operational efficiency in warehouses. The results of this research show that there is a difference in OMH produced in the selected proposed layout, namely IDR 23,748/day from IDR 49,085/day. This shows that there is a reduction in OMH of 52%